Determinants of Household Food Wasting Behavior: Applying the Theory of Planned Behavior - Fajar Wahyu Nugroho; Maswadi; Novira Kusrini (Jurnal Ilmu Pertanian Indonesia, 2025)
Every year, up to 1.3 trillion tons of global food produced for human use are lost or wasted. Consumer behavior is a major cause of food waste. In Indonesia, households generate approximately 38% of total food waste. The goal of this study is to evaluate at how attitudes toward behavior, subjective norms, perceived behavioral control, and intention to reduce food waste affect food waste behavior in households. The theory of planned behavior (TPB) was used to conduct the survey, which included 160 independent oil palm farmer homes. The collected data was then examined using Structural Equation Modelling (SEM) with the AMOS 24 program. The findings demonstrate the effectiveness of the TPB model in forecasting household food waste behavior. Attitude, subjective norm, perceived behavioral control, and goal to reduce food waste are the factors that influence household food waste behaviors. The study's findings show that perceived behavioral control is the most important predictor of food waste behavior. Furthermore, the findings demonstrate that attitudes and subjective norms can predict the intention to reduce household food waste. Meanwhile, the desire to eliminate food waste appears to be a strong predictor of one's attitude on the amount of food waste produced. Keywords: food waste, household behavior, SEM-AMOS, theory of planned behavior